Early cardiovascular multimorbidity in out- and in-patient care: age characteristics and medication therapy (data from the REKVAZA and REKVAZA-CLINIC registries) - E. Yu. Andreenko; M. M. Lukyanov; S. S. Yakushin; A. N. Makoveeva; A. N. Vorobiev; K. G. Pereverzeva; E. V. Kudryashov; V. G. Klyashtorny; V. A. Dindikova; A. A. Smirnov; S. A. Boytsov; O. M. Drapkina (Кардиоваскулярная терапия и профилактика, 2020)
Aim. To assess the age and sex characteristics, comorbidities and medication therapy in patients with early cardiovascular multimorbidity in out- and in-patient care.Material and methods. The REKVAZA registry includes 3,690 patients with hypertension (HTN), coronary artery disease (CAD), heart failure (HF), atrial fibrillation (AF) and their combinations, who applied to primary care facilities in Ryazan in 2012-2013. The hospital registry REKVAZA-CLINIC included 17,018 patients hospitalized due to cardiovascular disease (CVD) at the National Medical Research Center for Therapy and Preventive Medicine from April 2013 to March 2020. The groups of patients with early cardiovascular multimorbidity were compared according to two criteria: criterion 1 — age 18-49 years; criterion 2 — the age of men, 18-54 years; women, 18-64 years. The structure of CVD and related diseases, as well as cardiovascular therapy were analyzed.Results. The proportion of persons with early cardiovascular multimorbidity from the total number of patients with cardiovascular multimorbidity was as follows: using criterion 1 — 4,9% (145/2959) and 4,94% (571/11557) (p=0,66), criterion 2 — 29,0% (859/ 2959) and 18,8% (2168/11557) (p<0,0001), respectively. Using criterion 2, in contrast to criterion 1, the proportion of men with early multimorbidity was 2,7 times less in the REKVAZA registry (17,1 vs 45,5%; p<0,0001) and 1,8 times less in the REKVAZA-CLINIC registry (44,2 vs 80,9%; p<0,0001). Among individuals with >2 CVDs (HTN, CAD, HF, AF, myocardial infarction, acute cerebrovascular accident), the proportion of individuals with early development of each of the listed diseases was significantly higher in the out- and in-patient registries, when using criterion 2 (14-29%) compared to criterion 1 (2-2,5%). Among patients with early onset of CVD in the outpatient registry, when criteria 1 and 2 were used, the proportion of patients with cardiovascular multimorbidity was 41,8 and 62,7% (p<0,0001), respectively; in the inpatient registry — 34,1 and 45,5% (p<0,0001). That is, at the age of <50 years> 1/3 of patients were found to have combined CVDs. Using criterion 2, compared with criterion 1, the proportion of persons with HTN and concomitant CVD among all patients with early HTN was 1,5 times higher (62,8 vs 41,6%; p<0,0001) in the outpatient register and 1,3 times higher in the inpatient one (48,9 vs 37,5%; p<0,0001). The proportions of persons with HTN in combination with other CVDs were among all hypertensive patients aged <45 and <40 years: in the outpatient registry, 35,5% (61/172) and 33,3% (38/114) cases, respectively, and in the inpatient — 27,8% (215/772) and 26,5% (95/359), respectively. According to the data of both out- and inpatient registries, in patients with early development of HTN (<50 years of age) and concomitant CVDs, compared with those without such a combination, there was a greater number of noncardiac diseases (18,3 vs 7,0%; p=0,001), diabetes (12,9 vs 4,7%; p<0,0001), respectively. In the inpatient registry, in addition to diabetes, there was a greater proportion of people with gastrointestinal diseases (78,7 vs 73,2%; p=0,02) and obesity (37,9 vs 30,3%; p=0,004). Among patients <50 years of age, the prevalence of those taking appropriate medications was higher than in the group of patients meeting criterion 2 — 68,0% vs 63,2%, respectively (p=0,03).Conclusion. Early cardiovascular multimorbidity in the REKVAZA and REKVAZA-CLINIC registries was detected in 14-29% of the total number of combined CVD cases when using criterion 2 and only in 2-5% when using criterion 1. However, in relation to the total number of patients with early CVD development, individuals with cardiovascular multimorbidity make up the majority. It is preferable to use age <50 years as a criterion for early cardiovascular multimorbidity. But the criterion for the early development of HTN combined with other CVDs is appropriate to consider the age <40 years. Persons with early cardiovascular multimorbidity, especially at the age of 18-49 years, are the target group for the implementation of preventive measures.